Pro?le of Children Su?ering from Urinary Tract Infection: A Cross-Sectional Study - Pragya Prakash Chandra Khanna; Gaurang Dilipkumar Pabani (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Background : Present study was performed at a tertiary care centre in Gujarat, to discover the profile of the paediatric urinary tract infection (UTI) and to monitor vesicoureteric reflux (VUR) and renal scarring in these subjects. Subjects and Methods: Present Hospital based observational prospective study was performed in 150 clinical cases by using Random sampling method, performed at department of pediatrics, Tertiary care institute of Gujarat. Patients from the age of 1 month to 14 years presenting with urinary symptoms (dysuria, urgency, frequency, incontinence, hematuria and suprapubic pain) and those with fever without focus were enrolled in the study. History was noted and children clinically examined. Results: Out of total 150 cases, majority of cases were between 1 to 5 years followed by 6-10 year, more than 10 years and less than 1 year. Female were more affected than male children. Out of total 150 cases, majority of patients i.e., 65% were from middle socioeconomic status According to presenting history, maximum patients presented with abdominal symptoms (70%), urinary symptoms (22%), followed by respiratory symptoms in 19% cases, CNS symptoms (7%) and non-specific symptoms in 48% cases. Fever was the most common presenting complaint. Conclusion: UTI differs with age and gender and, so, widespread assessment is necessary in boys under one year of age with UTI. Females were extra usually exaggerated than males. Fever being most ordinary presenting symptom follows by vomiting and pain abdomen.